Relations between specific athleticism and morphology in young basketball players - Čović, Nedim; Čaušević, Denis; Alexe, Cristina Ioana; Rani, Babina; Dulceanu, Corina Ramona; Abazović, Ensar; Lupu, Gabriel Stanica; Alexe, Dan Iulian (Frontiers in Sports and Active Living, 2023)
Introduction Basketball is a fast-paced intermittent team sport, wherein the players must exhibit different morphologies and fitness levels depending on their position. The aim of this study was to assess the differences in the athleticism of basketball players by playing positions and in its relations with body composition and anthropometric measures. It was hypothesized that calculated athleticism has stronger and better predictive relations with morphology compared to motoric tests alone. Methods 47 basketball players were divided into three groups according to playing position [guards (n = 14), forwards (n = 22), centers (n = 11)]. Body composition and anthropometrical measurements were done for all players. Athleticism was presented in terms of overall (OFS), jumping (JFS) and sprinting (SFS) fitness scores. Results Fitness scores were found to be more strongly related to body composition and anthropometry measurements than motoric tests alone. All three fitness scores were moderate to strongly correlated with skinfold thickness and fat percentage, while body height, fat-free mass, and lean body mass were positively correlated. Significant differences in athleticism fitness scores were found between guards and other groups. Forwards displayed superior athleticism in power and sprint abilities when compared to guards and centers. Multivariate logistic regression revealed that fat percentage, lean muscle mass, skinfold thickness, and arm span exhibited strong predictive capabilities in relation to athleticism scores. Conclusions Coaches and practitioners should be aware that athleticism includes a multitude of components, and they should use athleticism assessments before designing training regimens that are tailored to each position's unique needs.